Unusual Ferromagnetic Band Evolution and High Curie Temperature in Monolayer 1T-CrTe2 on Bilayer Graphene - Park Kyoungree; Lee Ji-Eun; Kim Dongwook; Zhong Yong; Farhang Camron; Lee Hyobeom; Im Hayoon; Choi Woojin; Lee Seha; Mun Seungrok; Kim Kyoo; Choi Jun Woo; et al. (Wiley - V C H Verlag GmbbH & Co., 2025)
2D van der Waals ferromagnets hold immense promise for spintronic applications due to their controllability and versatility. Despite their significance, the realization and in-depth characterization of ferromagnetic materials in atomically thin single layers, close to the true 2D limit, has been scarce. Here, a successful synthesis of monolayer (ML) 1T-CrTe2 is reported on a bilayer graphene (BLG) substrate via molecular beam epitaxy. Using angle-resolved photoemission spectroscopy and magneto-optical Kerr effect measurements, that the ferromagnetic transition is observed at the Curie temperature (TC) of 150 K in ML 1T-CrTe2 on BLG, accompanied by unconventional temperature-dependent band evolutions. The spectroscopic analysis and first-principle calculations reveal that the ferromagnetism may arise from Goodenough-Kanamori super-exchange and double-exchange interactions, enhanced by the lattice distortion and the electron doping from the BLG substrate. These findings provide pivotal insight into the fundamental understanding of mechanisms governing 2D ferromagnetism and offer a pathway for engineering higher TC in 2D materials for future spintronic devices.